Studi Performa Panel Surya 100 WP Menggunakan Software Homer Di Universitas Pamulang - simanjuntak, Refor mangasi; Triyanto, Aripin (Jurnal Elektro, 2024)
Studies on designs and systems for solar panels are currently continuing to be developed. One application is to design a Homer-based solar power generation system (PLTS) with a solar panel capacity of 100 Wp and analyze the system performance at different loads. This research was conducted to determine the amount of power that solar panels can produce, load consumption, and determine a suitable system configuration to meet electricity needs at different loads. The method used is design, determining parameters on the homer and creating a simulation with loading. The research results show that the amount of power that can be produced by solar panels is 75,2kWh/year and can meet electricity needs at different loads. It is hoped that this research can be a solution to optimize the use of solar energy on a small scale and support renewable energy programs in Indonesia.